Pengaruh Kombinasi Silika dan Asam Humat terhadap Ketersediaan Nitrogen dan Pertumbuhan Tanaman Padi pada Tanah Berpasir - Rusyla Dwi Rahayu; Wanti Mindari; Moch. Arifin Moch. Arifin (Fakultas Pertanian Universitas Padjadjaran, 2021)
Sandy soils have high macropores and low nutrient availability. This condition is caused by the soil matrix which has no negative charge, so that nutrients are easily lost due to washing. Nitrogen loss has been reported to reduce rice production by 6.10%. The research aims to examine the application of humic acid and silica to increase the availability of nitrogen nutrients. Humic acid from compost and silica from rice husk is expected to increase the negative charge of the soil so that can adsorbnutrient ions such as nitrogen. The research was carried out from March to September 2021 in the greenhouse and laboratory of the Faculty of Agriculture, National Development University